Discovery of pararealgar and semi-amorphous pararealgar in Rembrandt's The Night Watch: analytical study and historical contextualization - De Keyser, Nouchka; Broers, Fréderique T. H.; Vanmeert, Frederik; van Loon, Annelies; Gabrieli, Francesca; De Meyer, Steven; Gestels, Arthur; Gonzalez, Victor; Hermens, Erma; Noble, Petria; Meirer, Florian; Janssens, Koen; et al. (Heritage science, 2024)
This article reports on the discovery of pararealgar and semi-amorphous pararealgar in Rembrandt's masterpiece The Night Watch . A large-scale research project named Operation Night Watch was started in 2019 . A variety of non-invasive analytical imaging techniques, together with paint sample research, has provided new information about Rembrandt's pigments, materials, and techniques as well as the current condition of the painting. Macroscopic X-ray fluorescence, macroscopic X-ray powder diffraction and reflectance imaging spectroscopy identified the presence of arsenic sulfide pigments and degradation products of these pigments in the doublet sleeves and embroidered buff coat worn by Lieutenant Willem van Ruytenburch (central figure to the right of Captain Frans Banninck Cocq). Examination by light microscopy of two paint samples taken from this area shows a mixture of large sharp-edged tabular yellow and orange to red pigment particles, and scanning electron microscopy-energy dispersive X-ray analysis identified these particles as containing arsenic and sulfur. Using micro-Raman spectroscopy, the yellow particles were identified as pararealgar, and the orange to red particles as semi-amorphous pararealgar. Synchrotron-based X-ray diffraction allowed visualization of the presence of multiple degradation products associated with arsenic sulfides throughout the paint layer. The discovery of pararealgar and semi-amorphous pararealgar is a new addition to Rembrandt's pigment palette. To contextualize our findings and to hypothesize why, how, and where Rembrandt obtained the pigments, we studied related historical sources. A comprehensive review of historical sources gives insight into the types of artificial arsenic sulfides that were available and suggests that a broader range of arsenic pigments could have been available in Amsterdam in the seventeenth century than previously thought. This is supported by the use of a very similar mixture of pigments by Willem Kalf (1619–1693), a contemporary artist based in Amsterdam. Together with the condition of the particles in the paint cross sections, this brings us to the conclusion that Rembrandt intentionally used pararealgar and semi-amorphous pararealgar, together with lead–tin yellow and vermilion, to create an orange paint.